2016
DOI: 10.1016/j.vetimm.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Infection with equine infectious anemia virus vaccine strain EIAVDLV121 causes no visible histopathological lesions in target organs in association with restricted viral replication and unique cytokine response

Abstract: The live equine infectious anemia virus (EIAV) vaccine strain EIAVDLV121 was developed by in vitro attenuation of a virulent strain, EIAVLN40, in the 1970s, and it has been demonstrated to induce protective immunity under laboratory and natural EIAV infection conditions. The detailed biological features of this attenuated virus remain to be further investigated. Experimental inoculation with EIAVDLV121 did not result in clinical symptoms even with immunosuppressive treatment in our previous studies. Here, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Our previous research found that EIAV DLV34 can induce a host inflammatory storm to cause severe pathological injury but that EIAV DLV121 can induce only a weak inflammatory response. In addition, the apoptosis induced in eMDMs infected with EIAV DLV121 was significantly higher than that induced in eMDMs infected with EIAV DLV34 (4,5). This finding suggests that the host cellular inflammatory responses and apoptosis are closely related to EIAV pathogenicity and the protective mechanisms of the attenuated vaccine.…”
mentioning
confidence: 87%
“…Our previous research found that EIAV DLV34 can induce a host inflammatory storm to cause severe pathological injury but that EIAV DLV121 can induce only a weak inflammatory response. In addition, the apoptosis induced in eMDMs infected with EIAV DLV121 was significantly higher than that induced in eMDMs infected with EIAV DLV34 (4,5). This finding suggests that the host cellular inflammatory responses and apoptosis are closely related to EIAV pathogenicity and the protective mechanisms of the attenuated vaccine.…”
mentioning
confidence: 87%
“…Lebih lanjut Ma et al (2011) melaporkan bahwa vaksin hidup yang telah dilemahkan dinilai sangat efektif untuk mencegah penyakit, terutama saat terjadi wabah. Penelitian yang telah dilakukan oleh Liu et al (2016), menunjukkan bahwa virus strain yang digunakan pada vaksin EIA mampu memberikan proteksi yang optimum, dan tidak menimbulkan lesi pada organ kuda secara histologi.…”
Section: Upaya Pencegahan Dan Pengendalian Penyakitunclassified